2019
DOI: 10.1039/c9cc08069d
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 direct detection in human serum by time-gated fluorescence imaging

Abstract: A new time-gated fluorescence-based imaging method to analyse microRNAs directly from human serum using dynamic chemistry labelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Prompted by these current analytical limitations, our group developed seqCOMBO, a new method to overcome the inability of current technology to analyse miRNAs without affecting proteins. In seqCOMBO, our DCL transformative technology to interrogate miRNAs [17][18][19][20][27][28][29][30][31][32][33] was combined with an antibody-dependant method on the Luminex MAGPIX system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prompted by these current analytical limitations, our group developed seqCOMBO, a new method to overcome the inability of current technology to analyse miRNAs without affecting proteins. In seqCOMBO, our DCL transformative technology to interrogate miRNAs [17][18][19][20][27][28][29][30][31][32][33] was combined with an antibody-dependant method on the Luminex MAGPIX system.…”
Section: Discussionmentioning
confidence: 99%
“…This first step, to hybridise the miR-122, was performed in a 96-well plate using a microplate orbital at 700 rpm for 1 h at 40 • C. After the hybridization, the DGL-122 beads were washed three times with the wash buffer. The DGL-122 beads were resuspended in 50 µL of assay buffer containing 5 µM SMART-C biotin and 1 mM sodium cyanoborohydride [17][18][19][20][27][28][29][30][31][32][33]. The 96-well plate was shaken at 700 rpm at 40 • C for 1 h. The beads were washed three more times and incubated with 70 µL of 2 µg/mL SA-PE for 5 min at 40 • C while being shaken at 700 rpm.…”
Section: Calibration Curve For Mir-122 Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…( 18 ) proposed a biosensor able to analyse complete mRNAs, based on a bead-based silicon photonic resonator in conjunction with chaperone probes to reduce the mRNA secondary structure and enhance the access to the target. There are also biosensors focusing on the detection of specific miRNAs and mRNAs or even multiplexed detection of nucleic acids that have a great interest for diagnosis ( 19–21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, only a few uorescent probes have achieved both high intensity and long lifetime. [13][14][15] In recent years, it was reported that bright and long-lived uorescence can be obtained from the excimer state 13,[16][17][18][19] that was conventionally thought to be the cause of quenching due to the low-energy excimer trap states with forbidden radiative transition and activated non-radiative process. [20][21][22][23][24] However, most of these reports were in the solid state, where the molecular movement is suppressed and the luminescence occurs in a single crystal.…”
mentioning
confidence: 99%